Figurative Language in Selected Poem of Louise Gluck - Muhammad Taufik; Rianti G; Nirwana Nirwana (ASHLITION : Ash-Shahabah English Literature, Linguistics, & Education, 2023)
The research aims to figure out what kind of figurative language is contained in Louise Gluck chosen poem and to find out the meaning of Louise Gluck chosen poem. The method used in this study is a qualitative descriptive method. The data source of this research is a selected poem by Louise Gluck, then analyzed using the theory by Keraf. The results of research conducted on two selected poems by Louise Gluck entitled Crossroads and Sunset, the researchers found that there were 16 figurative languages. This finding is of course based on the scope of the research which only analyzes 5 figurative languages, namely: simile, metaphor, hyperbole, personification and synecdoche. Then based on the meaning using denotative and connotative theory, the researcher found 7 lines containing denotative meaning and 13 lines containing connotative meaning.